Accurate energy consumption for comparison of climate change impact of thermal and electric vehicles. (1st April 2023) - Desreveaux, A.; Bouscayrol, A.; Trigui, R.; Hittinger, E.; Castex, E.; Sirbu, G.M.
Abstract: Performing a climate impact assessment of vehicles is essential for comparing different powertrain options during an entire vehicle life. Life Cycle Assessment (LCA) is used to estimate these effects over a vehicle's lifecycle, including manufacturing, usage, and end-of-life phases. LCA comprises several indicators, such as the Global Warming Potential (GWP). Generally, LCA or GWP studies use manufacturer-reported standard cycle data to estimate the energy consumption of vehicles. In this article, we develop diesel, gasoline, and electric vehicle simulation tools using the Energetic Macroscopic Representation formalism to evaluate that practice. These simulations are validated with actual, measured driving cycles. The simulations are then used to compare the calculated GWP from real, measured driving cycles relative to standard driving cycles used as industry benchmarks. The results show that standard driving cycles consistently underestimate the benefit of switching from fossil fueled vehicles to electric vehicles. Finally, a sensitivity analysis of the battery life duration is included in this work. It shows that the replacement or second life of batteries is also a key parameter in the GWP advantages of electric vehicles. Highlights: Global Warming Potential of European conventional and electric small cars are compared. Benefits of EVs are larger in real driving cycles instead of standard ones. Sensitivity analysis is done for EV battery life duration. Battery second life increases the benefits of the electric vehicles up to 43%.